Madame de Pompadour painted pink - Albinson, Cassandra ca. 20. Jh (Harvard Art Museums, 2022)
Francois Boucher's 1750 half-length portrait of Madame de Pompadour-influential court figure and mistress to King Louis XV-has been the subject of much art historical attention, particularly with regard to gender and representation. Building on that foundation, this volume turns toward an underappreciated aspect of the portrait: the use and significance of the color pink. Four scholarly essays, including one by noted Boucher expert Mark Ledbury, establish a framework that connects Pompadour's fondness and promotion of the color, Boucher's artistic association with the color, and developments in the material basis of the color, including its application in other media such as porcelain. This engaging close look offers new ways to understand the portrait, revealing its links to motherhood and sentiment, race and the transatlantic slave trade, and the crosscurrents of natural history and scientific discovery.
Keywords: Boucher, François -- 1703-1770 -- Bildnis der Marquise de Pompadour; Rosa; Aufsatzsammlung